Assessment of the Ecowas Protocol on Free Movement of Persons, Right of Residence and Establishment (The Case of Elubo Border). - Marmon-Halm, N.N.K.M. (University of Ghana, 2018)
The main aim of the study was to assess the implementation of the ECOWAS Protocol on free movement of persons, rights of residence and establishment. For this, the mixed method of data collection was used which formed the basic design for the study. Using the convenient method, 84 travellers and 30 officers were sampled to respond to structured questionnaires and semi interview questions respectively. Data was analysed using quantitative and qualitative methods and the results triangulated. Results of the study indicated that most respondents do not have any knowledge of the ECOWAS Protocol whereas a few of the respondents affirmed to their having knowledge in the Protocol. Those who are familiar with the Protocol indicated that it is useful and that it is working for its purpose. Similarly, most respondents do not know how the implementation of the ECOWAS Protocol is done. According to officers at the borders, one basic challenge facing them as border officials is the issue of language barrier. The sub-region is made up of Anglophone and Francophone countries. Ghanaian officials therefore find it difficult to communicate with travellers from other countries other than English speaking countries. Likewise, other officials like those at La Cote D’Ivoire have problems communicating with travellers from English speaking countries. It was recommended that Officers that will be put at the borders should be those that could speak other foreign languages especially French and English. Those that will be on duty should always have at least one person among them who could speak such languages. This will facilitate effective communication. Authorities of member states should endeavour to have a common identification document and even common ECOWAS currency which will facilitate bilateral trade, thereby helping the Protocol achieve its objective of regional integration and trade.
Thesis (MA)
Keywords: triangulated; ECOWAS Protocol; Implementation; Anglophone; Francophone